Distribution and host plant associations of Megachile (Pseudomegachile) lanata (Fabricius, 1775) (Megachilidae) in Pothohar, Pakistan (Zoo Botanica, 2023)
Solitary Megachile lanata (Fabricius) are important pollinator of a variety of plants including horticultural, ornamental, aromatic and agricultural crops based on their prevalence and floral host plant range. Their presence can greatly increase the yield and quality of the crops they pollinate. Explore the occurrence and floral host plant range of Megachile (Pseudomegachile) lanata within the Pothohar plateau, Punjab, Pakistan. The specimens of Megachile lanata (Fabricius) were collected on a monthly basis from various agricultural and all other types of landscapes, such as forests, urban areas and natural habitats in the Pothohar plateau of Punjab, Pakistan during 2021-2022. The individuals of this bee were collected with an aerial net. Present study investigate seasonal population and distribution range of M. lanata. Herein, we have observed twelve host plants in various localities of study area. This is an invasive species and one distinct feature is the inclusion of brief diagnostic information, details about host plants as well as information on ecology and current distribution in Pakistan. This data will contribute to a better understanding of solitary Megachile lanata (Fabricius) bee species diversity and abundance, which is crucial for maintaining the health of ecosystems, especially those in agro-ecosystems on Pothohar Plateau of Punjab, Pakistan.
Keywords: biodiversity; foraging behavior; pollination ecology; megachilidae; pothohar; pakistan